A motivational training program for secondary physical education teachers based on the circumplex model: a study protocol of a randomised controlled trial - García-Cazorla, Javier; Sevil-Serrano, Javier; García-González, Luis; Abós, Ángel (Frontiers in Public Health, 2024)
In most self-determination theory (SDT) research, improving (de)motivating teaching styles provides numerous benefits for students and teachers, although there is less evidence of the latter.Although the recent circumplex model provides a fine-grained picture of the different (de)motivating teaching styles (i.e., autonomy support, structure, control, and chaos) that physical education (PE) teachers can use in their lessons, no previous motivational training programs have been based on this model. Moreover, all SDT-training programs have been implemented through different group sessions, but individual sessions have not been delivered. This study outlines the protocol of a motivational training program, derived from the circumplex model, designed to enhance motivating teaching styles (and prevent or decrease demotivating teaching styles) among PE teachers. Consequently, this program seeks to improve motivational variables and influence (mal)adaptive outcomes in both teachers and students. A randomised controlled trial design with a mixed-method approach. At least 16 secondary PE teachers will be assigned to either an experimental group or a control group, together with some of their students. The training program comprises four face-to-face group sessions and two follow-up sessions (one individual and one group session). PE teachers will learn how to support autonomy and provide structure, as well as to be less controlling and chaotic towards students. Over approximately five months, teachers will implement these motivational strategies during their PE classes. Different (de)motivating teaching styles, motivational variables, and (mal)adaptive outcomes will be assessed in both PE teachers and their students at three distinct points: before the training program (T1), during the intervention (T2), and at the end of the intervention (T3). Additionally, two discussion groups involving all experimental PE teachers will be held (one following the training program and another at the end of the intervention). The results from this study could be useful for developing motivational training programs for in-service PE teachers. This study was registred in ClinicalTrials.gov (Identifiers: NTC06479369 / Unique protocol ID: PID2021-127897NA-I00).